Techno-economic analysis of catechin mix manufacture from Camellia sinensis leaves using green extraction technology - Adeyi Oladayo (Association of the Chemical Engineers of Serbia, 2021)
This work designed, modeled and performed economic analysis of the base case extraction and recovery of catechin mix (CM) from Camellia sinensis leaves (CSL) using deep eutectic solvent (DES) and microwave assisted extraction (MAE) with the assistance of SuperPro Designer software. Techno- -economic analysis of three commercial scales of manufacture was also investigated and compared using profitability parameters. Sensitivity and uncertainty analyses were further carried out on the most viable commercial scale to determine input variable(s) of highest significance on the profitability of the process. The 3.30 kg CM/batch is the most economically desirable scale with return on investment of 324.65%, payback period of 0.31 years, internal rate of return of 163.83% and net present value of $1,059,595,224. Out of the input variables selected for the sensitivity and uncertainty analyses, CSL and DES costs have the least effect on the selected profitability parameters of the process.